1992
DOI: 10.1364/ao.31.004829
|View full text |Cite
|
Sign up to set email alerts
|

Laser marking of thin organic films

Abstract: The threshold marking response of a laser-irradiated dye-polymer thin film is described by a simple, thermally thresholding model. The apparent loss of thermal reciprocity is related to active reflectance changes during mark formation. It is shown that incorporation of measured differences between physical and optically detected mark lengths are required for the model to accurately replicate the subsequent marking response. A theoretical expression is derived that permits the estimation of media thermal diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…There are many kinds of investigation on laser processing for the different materials that including: Bartholomeusz and Gupta (1992) proposed investigation thermally threshold model of laser irradiation on dye-polymer thin films. Peligrad et al (2001) proposed investigation the development an analytic model for quality control of laser marking and laser engraving of inhomogeneous materials using a high-power diode laser (HPDL).…”
Section: Introductionmentioning
confidence: 99%
“…There are many kinds of investigation on laser processing for the different materials that including: Bartholomeusz and Gupta (1992) proposed investigation thermally threshold model of laser irradiation on dye-polymer thin films. Peligrad et al (2001) proposed investigation the development an analytic model for quality control of laser marking and laser engraving of inhomogeneous materials using a high-power diode laser (HPDL).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been undertaken to investigate laser ablation in vacuum or ambient air. [1][2][3][4][5] On the other hand, only a few studies have been reported for laser ablation at the solid-liquid interface. [6][7][8][9][10] Recently, some studies have shown promoted efficiency for material surface processing by the water confinement regime ͑WCR͒ configuration.…”
mentioning
confidence: 99%
“…The method is non-contact, does not require a special working environment and can be easily automated and integrated into production lines. [5,6,7,14,15] The aim of the present study is to analyse the capabilities of one industrial CO2 laser system for marking eggs, to determine the optimal operating intervals for power and processing speed to achieve optimal marking contrast [8].…”
Section: Introductionmentioning
confidence: 99%